Taxpayer Compliance in Paying Rural and Urban Land and Building Tax (PBB-P2) in the Perspective of the Theory of Planned Behavior - Benny Oktaviano; Dian Sulistyorini Wulandari; Syifa Fauziyyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of economic level, tax knowledge, fiscus service, and fines on taxpayer compliance in paying Land and Building Tax of Rural and Urban Areas (PBB-P2) in East Cikarang District, Bekasi Regency. The types of data used in this study are secondary data and primary data obtained by distributing questionnaires to taxpayers in East Cikarang District using a random sampling method. The analysis technique used in this study was the multiple linear regression technique. The results show that (1) Economic level has no effect on taxpayer compliance in paying PBB-P2, (2) Tax knowledge has a positive and significant effect on taxpayer compliance in paying PBB-P2, (3) Fiskus services have a positive and significant effect on taxpayer compliance in paying PBB-P2, (4) Fines have a positive and significant effect on taxpayer compliance in paying PBB-P2, (5) Economic Level, Tax Knowledge, Fiscal Services, and Fines have a simultaneous effect on taxpayer compliance in paying PBB-P2.